Clinical Characteristics of Covid-19 in New York City - Goyal, Parag; Choi, Justin J; Pinheiro, Laura C; Schenck, Edward J; Chen, Ruijun; Jabri, Assem; Satlin, Michael J; Campion, Thomas R; Nahid, Musarrat; Ringel, Joanna B; Hoffman, Katherine L; Alshak, Mark N; et al. (The New England journal of medicine, 2020)
In this series of 393 consecutive patients admitted with Covid-19 to two New York City hospitals from March 3 to March 27, a third of patients received invasive mechanical ventilation, 10% of patients died, and 24% were still hospitalized as of April 10.